Experimental study of the slab effects on the performance of RC frame under the loss of an interior column scenario - Lim, Zhi Hao. (2013)
Although progressive collapse is low possible event, the asset and life loss due to progressive collapse can be very catastrophic. Thus, it is necessary to study the performance of RC structures against progressive collapse. To date, the progressive collapse performance of building is studied by assuming one or several columns in some specific locations had missed. Several numerical and experimental studies had been conducted. However, majority of these studies are focused on the beam-column substructures without including the contribution of RC slabs for progressive collapse resistance. Several decades had indicated that there is second resistance mechanism could be developed in the slab to resistant the collapse of RC slabs. It is called compressive/tensile membrane actions. However, previous studies regarding compressive/tensile membrane actions are only concern one-bay of the slab under service load condition. To date, no experimental tests had been carried out to quantify the compressive/tensile membrane actions in resisting progressive collapse (several bay and some of the column is missed). Thus, two beam-column-slab specimens (S1 and S2) were tested in this study for above purpose. Moreover, in order to evaluate the slab effects on the performance of RC beam-column substructure in resisting progressive collapse, another two specimens (T1 and T2) are tested for comparison. It was found that RC slab could increase the initial stiffness and yield strength of RC frames under the loss of an interior column scenario up by 46.9% and 56.5%, respectively. Moreover, at large displacement stage, the tensile membrane action developed in the slab and catenary action developed in the beams would increase the yield strength of beam-column-slab specimens up by 102.1%.